The wonderful world of seals and whales - Crow, Sandra Lee, 1948- ([Washington, D.C.] : National Geographic Society, 1984)
Text and photographs present information about seals and whales.
Keywords: Southeast Asian Linguistics Society. -- Meeting; Seals (Animals) -- Juvenile literature; Whales (Animals) -- Juvenile literature; Whales